The Effect of Dual Task Attention Instruction on the Static and Dynamic Balance of the Ahwaz Elderly - saeed alboghbish; shahla zahednejad; mehrdad sharifi; sima razaghi; Sjad prsaei (فصلنامه دانشگاه علوم پزشکی جهرم, 2018)
Introduction: improvement ofthe elderly balance by Exercise interventions have great importance. The purpose of this study was investigate effect of dual task attention instruction on static and dynamic balance ofthe elderly in Ahvaz residency. This study is quasi-experimental and purposeful research. The statistical population of this study was 60 years old adult people living in Salehin residency of Ahvaz. Twenty persons who had the criteria for entering the research were selected by available sampling method and participated voluntarily after obtaining consent. A week after the pre-test, the training sessions started and lasted for three consecutive sessions. Inthe dual task attention group, the instruction was that during the execution ofthe static and dynamic balance task a secondary cognitive assignment (Countdown numbers) were performed. In the control group no cognitive dual task were given. After the end of the training sessions, post-test was performed. To Comparison between groups Ancova with p <0.05 significant level was used. Results: The results showed that there was a significant difference between the experimental and control groups in the static balance and dynamic balance. Using dual tasks improved static balance but had a weaken effect on the dynamic balance of elderly people. Conclusion: The results of this study confirmed that a period of dual task attention instruction improves the static balance in the elderly but has a weaken effect on the dynamic balance of the elderly; therefore, it suggested dull task method to improve static balance in Elderly.